CANDIDATE CLUSTERS OF GALAXIES AT z > 1.3 IDENTIFIED IN THE SPITZER SOUTH POLE TELESCOPE DEEP FIELD SURVEY - Rettura, A.; Martinez-Manso, J.; Stern, D.; Mei, S.; Ashby, M. L. N.; Brodwin, M.; Gettings, D.; Gonzalez, A. H.; Stanford, S. A.; Bartlett, J. G. (The Astrophysical journal, 2014)
We present 279 galaxy cluster candidates at z > 1.3 selected from the 94 deg[sup 2] Spitzer South Pole Telescope Deep Field (SSDF) survey. We use a simple algorithm to select candidate high-redshift clusters of galaxies based on Spitzer/IRAC mid-infrared data combined with shallow all-sky optical data. We identify distant cluster candidates adopting an over-density threshold that results in a high purity (80%) cluster sample based on tests in the Spitzer Deep, Wide-Field Survey of the Bootes field. The rich data set will allow direct or stacked measurements of Sunyaev-Zel'dovich effect decrements or X-ray masses for many of the SSDF clusters presented here, and enable a systematic study of the most distant clusters on an unprecedented scale. We measure the angular correlation function of our sample and find that these candidates show strong clustering.